2016
DOI: 10.1371/journal.pone.0151052
|View full text |Cite
|
Sign up to set email alerts
|

Trends from 2002 to 2010 in Daily Breakfast Consumption and its Socio-Demographic Correlates in Adolescents across 31 Countries Participating in the HBSC Study

Abstract: Breakfast is often considered the most important meal of the day and children and adolescents can benefit from breakfast consumption in several ways. The purpose of the present study was to describe trends in daily breakfast consumption (DBC) among adolescents across 31 countries participating in the HBSC survey between 2002 to 2010 and to identify socio-demographic (gender, family affluence and family structure) correlates of DBC. Cross-sectional surveys including nationally representative samples of 11–15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
73
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 40 publications
(63 reference statements)
9
73
2
3
Order By: Relevance
“…Several studies demonstrated that SES plays one of the key roles in the development of healthy eating habits in children [1,17], which tend to be carried into adulthood [18,19,20]. Significant associations have been documented between parental SES and the consumption of breakfast [7,9,21,22], a morning snack [9], dinner [21], fruit and vegetables [7,21,23,24,25] and dairy products (low and full-fat milk/yoghurt, chocolate milk, low and full-fat cheese and feta cheese) [7,25] in children and adolescents. Sweet beverages, processed and energy-dense foods have been inversely associated with family SES [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that SES plays one of the key roles in the development of healthy eating habits in children [1,17], which tend to be carried into adulthood [18,19,20]. Significant associations have been documented between parental SES and the consumption of breakfast [7,9,21,22], a morning snack [9], dinner [21], fruit and vegetables [7,21,23,24,25] and dairy products (low and full-fat milk/yoghurt, chocolate milk, low and full-fat cheese and feta cheese) [7,25] in children and adolescents. Sweet beverages, processed and energy-dense foods have been inversely associated with family SES [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, breakfast skipping is highly prevalent among adolescents . Nationally representative data demonstrate that nearly half (48.5%) of Canadian adolescents skip breakfast at least once a week . Other studies report comparable rates of breakfast skipping among Canadian youth .…”
mentioning
confidence: 99%
“…Commonly reported motives for breakfast skipping among youth include a lack of time and hunger in the morning . Adolescents have greater autonomy over their food choices and other behaviors than children, which may partially explain why breakfast consumption declines during this transitional period . Eating behaviors generally become more irregular and exploratory during adolescence, and are largely shaped by social influences .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…De plus, comme les adolescents prennent de l'autonomie, ce sont eux, plutôt que leurs parents, qui décident de la composition de leurs repas, du temps à leur consacrer et du moment auquel les prendre (Neumark-Sztainer et al, 1999). Il ressort d'une étude des données internationales de l'enquête HBSC qu'entre 2002 et 2010, la propension des jeunes âgés de 11 à 15 ans à prendre un petit-déjeuner chaque jour n'a sensiblement augmenté que dans 6 des 19 pays et régions à l'étude, mais a diminué dans 11 pays (Lazzeri et al, 2016).…”
Section: Activité Physique Et Retombées Non Scolairesunclassified